A Teacher's Inquiry into Bringing in Biliteracy in a Fifth-Grade English-Only Classroom - Stephanie Lynn Abraham (Networks: An Online Journal for Teacher Research, 2017)
This teacher inquiry project explored how I, a non-Spanish speaking teacher at the time, implemented critical, bilingual pedagogies to foster biliteracy development among my fifth-grade students. One, the project showed that students could further their biliteracy by incorporating their funds of knowledge through a family stories writing project. Two, many students were anxious about reading in Spanish, and dual poetry alleviated this due to its compactness and linguistic scaffolding. Finally, the project showed the continual issues of unequal power relations concerning bilingualism and biliteracy in US classrooms by showing how I failed to include languages other than Spanish in this project and how I succumbed to school pressures of high-stakes testing, often abandoning a critical, bilingual pedagogy in the process.
Keywords: biliteracy; teacher inquiry; critical pedagogy